AI‐Powered mental health chatbots: Examining users' motivations, active communicative action and engagement after mass‐shooting disasters. (29th September 2020) - Cheng, Yang; Jiang, Hua
Abstract: Chatbots are gaining their popularity in society and have triggered heated discussions in academia as well. Currently, few studies explored the applications of AI‐powered mental health chatbots in a mass‐shooting disaster context. Via integrating literature from multi‐disciplines such as crisis management, mental health and digital communication, this quantitative study intends to contribute to close this gap and explore the associations between perceived gratifications and protection motivations of using mental health chatbot services, active communicative action, and online and offline engagement behaviours of solving mental health problems after disasters. This study surveyed 1, 114 US participants who ever used chatbot services from top healthcare companies. Implications of the results enhance theoretical discussions on how artificial intelligence has shaped individuals' motivations, communicative action and engagement behaviour to treat mental health problems. This study also benefits professionals who want to learn more about chatbots for mental healthcare, crisis management and customer engagement.